2017
DOI: 10.1093/annonc/mdx279
|View full text |Cite
|
Sign up to set email alerts
|

International cancer seminars: a focus on esophageal squamous cell carcinoma

Abstract: The International Agency for Research on Cancer (IARC) and the US National Cancer Institute (NCI) have initiated a series of cancer-focused seminars [Scelo G, Hofmann JN, Banks RE et al. International cancer seminars: a focus on kidney cancer. Ann Oncol 2016; 27(8): 1382-1385]. In this, the second seminar, IARC and NCI convened a workshop in order to examine the state of the current science on esophageal squamous cell carcinoma etiology, genetics, early detection, treatment, and palliation, was reviewed to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
149
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 102 publications
2
149
0
1
Order By: Relevance
“…This results could be due to sparse data or may reflect that zinc concentrations could have been due to reverse causation. We are not aware of any previous prospective study which has investigated the association between toenail zinc status and ESCC . Nouri et al., showed that the nail zinc concentration was lower in 20 cases than 80 controls in a case–control study , and in the NIT intervention trial in China, the group that received oral zinc and retinol supplements experienced no reduction in ESCC risk .…”
Section: Discussionmentioning
confidence: 98%
“…This results could be due to sparse data or may reflect that zinc concentrations could have been due to reverse causation. We are not aware of any previous prospective study which has investigated the association between toenail zinc status and ESCC . Nouri et al., showed that the nail zinc concentration was lower in 20 cases than 80 controls in a case–control study , and in the NIT intervention trial in China, the group that received oral zinc and retinol supplements experienced no reduction in ESCC risk .…”
Section: Discussionmentioning
confidence: 98%
“…However, in other parts of the world squamous cell carcinoma of the esophagus is more prevalent and represents a significant public health problem. 43 A preliminary study in a population with a high prevalence of squamous cell carcinoma has shown the Cytosponge TM to be a feasible, safe and acceptable test for esophageal squamous dysplasia (ESD) with a sensitivity and specificity of 100% and 97% respectively when combined with p53 immunohistochemistry. 44 Further studies are on-going to explore the potential of the Cytosponge TM test combined with molecular and/or immunohistochemical biomarkers to detect ESD.…”
Section: Diagnosis Of Benign Esophageal Pathologies On Cytosponge Tmentioning
confidence: 99%
“…The highest ESCC incidence rates occur in Eastern to Central Asia, and along the Indian Ocean coast of Africa along the Great Rift Valley . The recognized ESCC hotspots exist within sharply defined regions, including Linxian, China; Golestan Province in Iran; Western Kenya and south to Malawi; the Eastern Cape province of South Africa; Calvados in France; Southern Brazil; and Uruguay …”
Section: Introductionmentioning
confidence: 99%
“…3 The recognized ESCC hotspots exist within sharply defined regions, including Linxian, China; Golestan Province in Iran; Western Kenya and south to Malawi; the Eastern Cape province of South Africa; Calvados in France; Southern Brazil; and Uruguay. 4 China has the highest ESCC incidence, accounting for 53% of ESCC cases worldwide. 2 EC mortality rates differ across different geographic areas in China, with significant gender discrepancy.…”
Section: Introductionmentioning
confidence: 99%